Practical applications for strengthning natural colors from teak leaves to improve the quality of cotton materials with sodium silicate (waterglass) - Khaliq, Abdul Malik (Faculty of Engineering, Universitas Negeri Yogyakarta, 2022)
ABSTRACTIndonesia is rich in cultural heritage and abundant natural resources that can be seen in many types of batik and other fabric crafts. It is also supported by various plants that can be used as natural dyes. Natural dyes or natural dyes refer to dyes derived from plant or animal parts, such as the roots, stems, and leaves. The weakness of natural dyes is that they are easy to wear off, so it needs a certain process called fixation. It is the process of locking or sealing a dye sticking to the fabric fibers. The waterglass will be beneficial to be used as a fixer since it is soft, sticky and made of melted sodium silicate crystals. This study aims to determine the final results of the waterglass fixation and determine the wearability, tensile strength, elongation, and absorption capacity of cotton cloth that has been fixed using waterglass. The result of waterglass fixation on cotton cloth using natural dyes in the dyeing process was quite good, unless the test section on soap wash. However, there was still a solution to overcome this problem by employing lerak water as the washing material. In the fading test process using gray schale and staining schale, all variations of fixation time obtained the same value, 2-3 (less) in the gray schale test and 4-5 (good) in the staining schale test. In testing the fabric's absorbency, all time variations got a value above 50%, indicating the results of waterglass fixation were quite good. The conclusion showed that the sample with a fixation time of 15 minutes got the best outcome for the strength and elongation of the fabric.